Estudo experimental sobre o efeito do estímulo musical na atenção de crianças e adolescentes com TDAH e com desenvolvimento típico - Camila Guimarães Mendes (2022)
OBJECTIVE: This study aimed to experimentally evaluate the effect of listening to music on the performance of children with Attention Deficit Hyperactivity Disorder (ADHD) and typically development (TD) children in an attentional task (Attention Network Test - ANT). METHODOLOGY: This is an experimental design study, with the protocol registered by the Brazilian Registry of Clinical Trials (U1111-12589039). The sample consisted of 76 boys aged 10 to 12 years, 34 with ADHD and 42 without a diagnosis of ADHD, matched for age, sex and socioeconomic status. Both groups performed the ANT (children's version) submitted to two randomized experimental conditions: with music (MU) and non-music (NMU). The evaluated outcome was the efficiency of the attentional networks (alert, orientation and conflict) and the general rate of errors made during the task. To characterize the sample, the Child Behavior Checklist 6-18 (CBCL/6-18), the Swanson Nolandand Pelham-IV (SNAP IV) and the Brazilian Economic Classification Criteria (CCEB) were applied. All children also performed the Conner's Continuous Performance Test (CCPT), which characterizes the child's attentional behavior. Repeated measures analyzes of variance (ANOVA) were performed to assess the effect of the experimental condition (MU versus SMU) on each group and the effect of the ADHD diagnosis. The commission errors and omissions obtained by the CCPT baseline care measure were included as covariates during the analyses. RESULTS: The analyzes showed that there was no significant difference between the groups and between the experimental conditions regarding attentional networks, however both groups had a reduced overall error rate when they performed the ANT in the condition with music. The results suggest that music affected the number of errors made during the attention task, but there was no direct effect on attentional networks. Thus, apparently there is no improvement in children's attention induced by listening to music. CONCLUSION: When children listen to music while performing tasks that require attention, they may feel more motivated and become more engaged in the task, which may lead to fewer mistakes. Our data are not conclusive since a sample enlargement is still necessary.